2019
DOI: 10.1523/jneurosci.2339-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Release Dynamics in the Tuberoinfundibular Dopamine System

Abstract: The relationship between neuronal impulse activity and neurotransmitter release remains elusive. This issue is especially poorly understood in the neuroendocrine system, with its particular demands on periodically voluminous release of neurohormones at the interface of axon terminals and vasculature. A shortage of techniques with sufficient temporal resolution has hindered real-time monitoring of the secretion of the peptides that dominate among the neurohormones. The lactotropic axis provides an important exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 72 publications
0
16
1
Order By: Relevance
“…The observed increase in instantaneous burst frequency after Trpc5 deletion could result in enhanced release of dopamine, thereby leading to prolactin deficiency. A recent report in male mice analyzing dopamine release dynamics at the median eminence using optogenetic stimulation and fast-scan voltammetry showed that dopamine output is maximal at action potential frequencies near 10 Hz within a single 5-s burst (21). However, these experiments did not test the impact of altered burst intervals within the time range of our findings.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The observed increase in instantaneous burst frequency after Trpc5 deletion could result in enhanced release of dopamine, thereby leading to prolactin deficiency. A recent report in male mice analyzing dopamine release dynamics at the median eminence using optogenetic stimulation and fast-scan voltammetry showed that dopamine output is maximal at action potential frequencies near 10 Hz within a single 5-s burst (21). However, these experiments did not test the impact of altered burst intervals within the time range of our findings.…”
Section: Discussioncontrasting
confidence: 69%
“…Thus, the firing properties of these neurons are likely to control the release of dopamine (17)(18)(19)(20) and therefore should be critical to determine reproductive success. A recent report investigating dopamine release dynamics confirmed the tight relationship between impulse activity and vesicular release in the tuberoinfundibular dopamine system (21).…”
mentioning
confidence: 77%
“…Confirmation that such close appositions represent true synaptic contacts must await ultrastructural studies or dual‐labelling for synaptic marker proteins. The neurochemical nature of such interactions is unknown although optogenetic studies suggest TIDA may inhibit adjacent neurones via the release of GABA or dopamine 14,35 . It is important to note that, although our investigation identifies TH‐expressing neurones within the arcuate nucleus, it does not confirm that all such neurones project to the median eminence and can thus be considered truly neuroendocrine in nature.…”
Section: Discussionmentioning
confidence: 64%
“…Although the physiological consequence of axonal projection origin is uncertain, it is interesting to note a dendritic origin has been suggested to promote back‐propagation of action potentials that may support the dendritic release of neurotransmitter 34 . In the current context, such an action could be important because the perisomatic release of dopamine, most probably from surrounding dendrites, has been shown to act via dopamine D2 receptors to inhibit the electrical activity of TIDA neurones, thus providing an ultrafast negative‐feedback mechanism 15,35 . It remains to be determined whether TIDA neurones with dendritic axonal origin play a disproportionate role in this process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation